A Formal Method for Detecting and Describing Cultural Complexity: Extending Classical Consensus Analysis. Issue 3 (August 2018) - Lacy, Michael G.; Snodgrass, Jeffrey G.; Meyer, Mary C.; Dengah, H. J. Francois; Benedict, Noah
The most widely used formal approach to culture, the cultural consensus theory (CCT) of Romney, Weller, and Batchelder, originally relied on a priori definitions of cultural groups to map their unity and diversity. Retaining key features of classical CCT, we provide techniques to identify two or more cultural subgroups in a sample, whether those groups are known in advance or not. Our method helps CCT practitioners connect to contemporary approaches to culture in anthropology and related disciplines, which emphasize complexity. We suggest that our method provides reasonable and easily implementable approximations of cultural unity and diversity within a sample. In pursuing these matters, we contribute to other ongoing efforts to bring CCT closer to contemporary theorizing on cultural multiplicity, thus rendering CCT potentially more useful to a wider range of practicing social scientists.